Ambiguitas Dan Pertumbuhan Ekonomi Di Kota Batam - Laia, Ikrar Niekha Elmawayanti; Salsabila, Lubna; Lodan, Karol Teovani (LPPM Universitas Putera Batam, 2024)
This research focuses on the economic development and unique institutional dynamics of Batam Island, Indonesia, since the 1970s. Initially developed under the governance of the Batam Authority (now BP Batam), Batam has experienced rapid population growth and significant economic expansion, making it one of Indonesia's fastest-growing cities. Despite economic downturns in other parts of Indonesia, Batam has consistently attracted foreign direct investment (FDI) and avoided recessions. The research examines the visionary leadership of B.J. Habibie, whose tenure transformed Batam into a major industrial hub with top-tier infrastructure, and the subsequent economic boom during the 1990s, marked by high growth rates. The study also addresses the dual institutional governance between the Batam City Government and BP Batam, which has led to conflicts in authority over licensing, land management, and assets. Efforts by the central government to maintain Batam's special status while implementing regional autonomy policies are explored, including the transition from a Free Trade Zone (FTZ) to a Special Economic Zone (SEZ) to attract investment. Methodologically, this research utilizes both secondary data from previous studies and primary data from surveys and interviews with Batam's stakeholders, including government representatives, business leaders, and community members. Findings highlight ongoing legal ambiguities, declining investment, economic growth challenges, and social issues. The study provides insights into the perspectives of experts and industry players on Batam's current problems and potential policy solutions for its future development.